The mechanism of immune dysregulation caused by porcine reproductive and respiratory syndrome virus (PRRSV) - Sinkora, Marek; Toman, Miroslav; Stepanova, Katerina; Stepanova, Hana; Leva, Lenka; Sinkorova, Jana; Moutelikova, Romana; Salat, Jiri; Srutkova, Dagmar; Schwarzer, Martin; Sinkora, Simon; Skalnikova, Helena Kupcova; et al. (Microbes and infection, 2023)
PRRSV is capable of evading the effective immune response, thus persisting in piglets and throughout the swine herd. We show here that PRRSV invades the thymus and causes depletion of T-cell precursors and alteration of the TCR repertoire. Developing thymocytes are affected during negative selection when they transit from the triple-negative to triple-positive stages at the corticomedullary junction just before entering the medulla. The restriction of repertoire diversification occurs in both helper and cytotoxic αβ-T cells. As a result, critical viral epitopes are tolerated, and infection becomes chronic. However, not all viral epitopes are tolerated. Infected piglets develop antibodies capable of recognizing PRRSV, but these are not virus neutralizing. Further analysis showed that the lack of an effective immune response against the critical viral structures results in the absence of a germinal center response, overactivation of T and B cells in the periphery, robust production of useless antibodies of all isotypes, and the inability to eliminate the virus. Overall, the results show how a respiratory virus that primarily infects and destroys myelomonocytic cells has evolved strategies to disrupt the immune system. These mechanisms may be a prototype for how other viruses can similarly modulate the host immune system.
Keywords: Lymhocytes; reprodukční a respirační syndrom prasat; prasata; Porcine respiratory and reproductive syndrome virus; virus reprodukčního a respiračního syndromu prasat; Swine; Epitopes; B-Lymphocytes; B-lymfocyty; Antibodies, Viral; Animals; Thymocytes; protilátky virové; epitopy; Porcine Reproductive and Respiratory Syndrome; T-cell precursors; zvířata